If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x+5=3(4x-5)
We move all terms to the left:
12x+5-(3(4x-5))=0
We calculate terms in parentheses: -(3(4x-5)), so:We get rid of parentheses
3(4x-5)
We multiply parentheses
12x-15
Back to the equation:
-(12x-15)
12x-12x+15+5=0
We add all the numbers together, and all the variables
20!=0
There is no solution for this equation
| x4−3=−5 | | (6x-9)(5x+10)=180 | | -15x+5=-10×+25 | | 5x–7=4x+3 | | x3-5x2+72=X3-4X2-9 | | –11x–6=-50 | | 15x+5=-10×+25 | | 5/8/w=40 | | (2x+4)=(6x-9) | | 50+12x+3+9x+1=180 | | x/41/2=12 | | 9x^2+8=116 | | (3x-2)=(2x-4) | | 5x-18=10x-3 | | 2(x–3)=3(x+1)+10 | | 62.50x+19.99=82.49 | | 4(x+5)+4=1/2(8x+48 | | 4(x+7)=360 | | x+2.25=10.50 | | -8=2x-4=8 | | 2-(3x+2)=8-x-4-2x | | -15d=4.5 | | 7(x+3=-49 | | -18=2+3(d+7) | | -2(2k-4)=24 | | 16−5a+2a−1=41−a | | 4x-10/5=2x+8 | | 3=1/5+x | | (5x-5)=(7x+1) | | -5-3x=56-28x | | -45=5/3+5b | | 2+3x=-2(6-2x) |